Specklinia dunstervillei, a New Species Long Confused with Specklinia endotrachys (Orchidaceae: Pleurothallidinae) - Karremans Lok, Adam Philip (2015)
Specklinia dunstervillei is described as a new species in recognition of the distinctness of a Venezuelan species related to and confused with Specklinia endotrachys. It was illustrated for the first time by G. C. K. Dunsterville in 1963 from a plant collected in Trujillo on the Cordillera de Merida. The newly named species can be easily recognized by its small habit, short leaves and small reddish-orange flowers, the non-ascending dorsal sepal and the obtuse petals that are shortly apiculate. Specklinia dunstervillei is formally described and illustrated once again and compared morphologically and genetically with its closest relatives.